Simulation of 500 MeV neutrons by using NaCl doped Water Cherenkov detector - Sidelnik, I.; Asorey, H.; Guarín, N.; Suárez Durán, M.; Berisso, M.G.; Lipovetzky, J.; Blostein, J.J. (Elsevier, 2020)
Fil: Sidelnik, I. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina